PERANCANGAN SISTEM INFORMASI REKAM MEDIS BERBASIS ELEKTRONIK RUMAH SAKIT KHUSUS PARU RESPIRA YOGYAKARTA - , GITA FITRIANTI G A P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The need for health care continues to increase pulmonary disease requires Special Hospital Pulmonary Respira Yogykarta as health care providers to provide excellent service (RSKP Respira Yogyakarta, 2014). Information systems can be used for data services information, particularly helpful in the establishment of policies and ease of implementation of field hospitals in Indonesia (Permenkes 82, 2013). In preliminary studies in Special Hospital Pulmonary Respira in January 2014, there has been no system-based electronic medical record information. Service activities and data processing is still done manually, ranging from patient registration, records on file patient medical records, registers, to the processing and presentation of data reporting. In addition, according to interviews with relevant personnel, revealed that the process makes the job much longer so that the data recapitulate the difficulties attendant end of each month. The development of increasingly complex information systems, the stages of development to become a one-way thing to do because it does not allow developers will always do looping back and reworking to get a satisfactory system users. Alternative development to overcome this limitation one with the prototype, where the developers will make design prototypes as quickly as possible and then ask for user feedback, so that the design of the prototype can be repaired quickly (Mcloed and Schell 2008). Produce a draft design of an electronic information management system based on the Special Hospital Pulmonary Respira Yogyakarta. Based on the interviews and analyzing the needs of the user, ie the registration clerk, filing clerk, nurses, doctors, laboratory institutions, the cashier, pharmacist, clerk coding, and reporting, the designers create a prototype system design, database, and display the corresponding interface to user requirements so as to facilitate activities that exist in the medical record unit and associated units. The results of the prototype are data flow diagrams, database tables, and user interface design. The results will be used as design considerations for building a system of medical record information.